THE CONTEXTS OF VASYL STEFANYK`S LETTER ABOUT THE STRUGGLE FOR THE UKRAINIAN UNIVERSITY - Nabytovych, Ihor (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The aim. To do a research through Vasyl Stefanyk’s epistles into his views on important social-historical and national-political phenomena and processes developing in Halychyna, namely in Lviv, at the beginning of the XXth century. It deals, first and foremost, with the need of starting a Ukrainian university in Halychyna as well as the participation of the metropolitan bishop of the Ukrainian Greek-Catholic Church Andrii Sheptytskyi in this important campaign. The research methods. With the aim of elucidating the declared social-political problem the following methods are employed: cultural-historical and biographical. The results. The article analyses the contexts of Vasyl Stefanyk’s letter, written in December 1901, to Father Kyrylo Hamorak. It is underlined that it is this letter that is an extremely interesting testimony of that epoch, that demonstrates the interest of both Stefanyk and his future father-in-law in political events concerning the struggle of the intelligentsia from Halychyna in order to create a Ukrainian university in Halychyna. The letter persuasively demonstrates the Ukrainian community’s special attention to the figure of Andrii Sheptytskyi, the metropolitan bishop of Halychyna. It is revealedthat the fight to create a Ukrainian university lasted throughout several decades but was not settled neither in the Austro-Hungarian Monarchy nor in the Second Partition of Rzeczpospolita. The matter of the Ukrainian university was that first political event, in which, as wrote Vasyl Stefanyk in his letter, Bishop Sheptytskyi demonstrated that he “adheres to Rusyny in a loyal way”. The scientific novelty: for the first time the attention is accentuated on Vasyl Stefanyk’s separate epistle, giving an insight into the multifaceted activities(foremost, social-political ones) of the writer and activist from Pokuttia, into his understanding of the need of establishing a Ukrainian university in Lviv and the participation of the metropolitan bishop Andrii Sheptytskyi in that.